القطاع السياحي في الجزائر بين إستراتيجية التنمية السياحية(2030sdat) وأهداف المتعاملين السياحيين -دراسة تحليلية باستخدام تقنية ماكتور- - مسكين, عبد الحفيظ; غريبي, فتحية; درويش, صفية (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة لتحليل العلاقات التي تربط مختلف المتعاملين السياحيين في الجزائر(توافق أو تعارض) ومدى تأثيرها على إمكانية تحقيق أهداف الإستراتيجية الوطنية لتنمية السياحة لأفاق 2030 وذلك بالاعتماد على تقنية ماكتور. وقد توصلت الدراسة إلى وجود تباين في درجة التقارب بين المتعاملين السياحيين من جد قوية إلى جد ضعيفة قد تصل أحيانا إلى تعارض، بما قد يؤثر سلبا على إمكانية تحقيق أهداف هذه الإستراتيجية، والتي أكدت الدراسة توزعها على ثلاث تكتلات، يضم كل تكتل مجموعة من المتعاملين السياحيين الذين تتوافق اهدافهم معها، وعليه توجد امكانية كبيرة لتحقيق اهداف استراتيجة التنمية السياحية في الجزائر لافاق 2030. The study aims at analyzing the relationship between the various tourism operators in Algeria (consensus or conflict) and the extent to which it affects on Potential for achieving the objectives of the national tourism development strategy for the Prospects 2030, based on the Mactor technique. The study identified there was a discrepancy in the degree of convergence between tourist operators from very strong to very weak it can sometimes going to conflict, this could have a negative impact on the achievement of the objectives of the Strategy, which the study confirmed that it is distributed into three groupings, each group includes a group of tourist operators whose objectives correspond to it. Thus, there is considerable potential for achieving the objectives of Algeria's tourism development strategy for the 2030 horizon
The tourism sector in Algeria, between the Strategy for Tourism Development (2030 SDAT) and the objectives of tourism operators - an analytical study using Mactor method
Keywords: نظام السياحة ; تنمية سياحية ; متعاملين سياحيين ; تقنية ماكتر ; جزائر